Titik sebagai Dasar Penciptaan Karya Seni - Hanny Wijaya (Humaniora, 2010)
Basic element of subject is point / dot. Line, shape, form (two-dimensional and three-dimensional), and other structures (geometrically or ornamentally) are formed by a group or more points. The variety of size and composition of point will illustrate the characteristic of that point. Interesting composition will create a great artwork. Despite of variety of the structure, the technical process of colour dots had been developed for a long time. During the development of Impressionism art, some artists had tried to apply the colour dots as a new technique, which called Pointillism. Georges Seurat was a pioneerof this technique development. Pointillism was well known as Divisionism or Chromoluminarism at that moment. This technique was using an additive method that combined basic pigment colours of red, green and blue to produce optical vibration in the painting, therefore the viewers would be able to reach the maximum luminosity in their vision. The existence of this technique had proved that science and art were able to support each other. The combination of logic and aesthetic were able to create many extraordinary artworks.